Transforming Slum Temporary Waste Disposal Sites (TPS) into Green TPS through Community-Based Eco-Urban Innovation - Trilusianthy Hidayat, Janthy; Mujio, Mujio; Lubis, Iskandar; Febriani, Yusi; Ramadhani, Salwa Nikmatul (Green Publisher Indonesia, 2025)
Karang Tengah Village has a variety of natural tourist destinations, currently the condition of the Waste Disposal Site (TPS) along the tourist route is still dirty and unorganized, thus reducing the aesthetic value and image of environmentally friendly tourist destinations and the role of the community (Paguyuban Local Guide Sentul) is not optimal. The purpose of the Community Service (PKM) activity in Karang Tengah Village is to obtain innovative community-based solutions to create a clean, aesthetic, and educational tourist destination environment. The approach used is participatory-educational and eco-urban micro intervention through five stages: socialization, training, technology implementation, mentoring, and replication. The results of the PKM are the transformation of a slum TPS into a Green TPS, training and mentoring on waste management, optimizing the role of the community in educating tourists to maintain a clean and aesthetic environment. The conclusion is that PKM through simple community-based interventions is able to transform a slum TPS into a Green TPS that supports the branding of the tourist village. The constraints faced are limited scope to one TPS location and one partner community and the contribution of the Green TPS model can be replicated in other tourist destination locations.